2018
DOI: 10.1002/hpm.2549
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic leadership and affiliative humor's role on service innovation: Lessons from Spanish public hospitals

Abstract: Despite literature identifies aspects that might promote innovation, the relationship between the leadership style and nurses' innovative behavior still remains unclear, and little research has provided evidence of this. To help advance in knowledge of effects of leadership on nurses' innovative behavior, we researched the effect of altruistic leadership on nurses' innovative behavior. In addition, the mediating role of affiliative humor in the relationship between altruistic leadership and nurses' innovative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…First, our results evidence that humble leadership has a direct and positive effect on nurses' innovative behaviour, supporting H1. Innovation activities often involve taking risks and facing difficulties (Salas‐Vallina et al, ; Zhong et al, ). One of the most important barriers to enact innovative behaviour is a fear of taking risks (Knol & van Linge, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, our results evidence that humble leadership has a direct and positive effect on nurses' innovative behaviour, supporting H1. Innovation activities often involve taking risks and facing difficulties (Salas‐Vallina et al, ; Zhong et al, ). One of the most important barriers to enact innovative behaviour is a fear of taking risks (Knol & van Linge, ).…”
Section: Discussionmentioning
confidence: 99%
“…Innovation activities often involve taking risks and facing difficulties (Salas-Vallina et al, 2018;Zhong et al, 2018). One of the most important barriers to enact innovative behaviour is a fear of taking risks (Knol & van Linge, 2009 Wang et al (2016) found that humble leadership is positive related to followers' creativity (the first component of innovative behaviour), and this positive effect is mediated by perspective taking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations